2018
DOI: 10.7189/jogh.08.020410
|View full text |Cite
|
Sign up to set email alerts
|

Costs associated with management of non-communicable diseases in the Arab Region: a scoping review

Abstract: BackgroundGlobal mortality rates resulting from non-communicable diseases (NCDs) are reaching alarming levels, especially in low- and middle-income countries, imposing a considerable burden on individuals and health systems as a whole. This scoping review aims at synthesizing the existing literature evaluating the cost associated with the management and treatment of major NCDs across all Arab countries; at evaluating the quality of these studies; and at identifying the gap in existing literature.MethodsA syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…From the 1,646 records, 198 full-text publications were assessed for eligibility. We identified additional 60 publications from the reference list of four systematic reviews [ 9 11 , 42 ]. Altogether, we extracted 3525 costs from 206 publications for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…From the 1,646 records, 198 full-text publications were assessed for eligibility. We identified additional 60 publications from the reference list of four systematic reviews [ 9 11 , 42 ]. Altogether, we extracted 3525 costs from 206 publications for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review of costs of NCDs in the Arab region shows that mortality and morbidity related to NCDs are rising in the region and across different income strata. However, due to paucity of data and methodological issues involved in estimating the cost of NCDs in most studies making any comparison has become difficult [17]. An estimate on economic burden of NCDs by the WHO and the United Nations Development Program (UNDP) in Saudi Arabia has shown that these diseases currently cost US$18.6 billion annually, which includes direct health care costs of US$5.5 billion and costs from lost productivity of US$ 13.1 billion [7].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the social cost of intangibles such as pain and suffering and care provided by non-paid caregivers as well as healthcare system administrative costs, cost of medications, clinician training programs, and research and infrastructure development were excluded in this study. A review based on studies conducted in the Arab region revealed that NCDs' management costs in the region are high; however, there is a large variation in the methods used to quantify the costs of NCDs in these countries, making it difficult to conduct any type of comparisons [17]. A study on cardio-vascular diseases (CVDs) in Saudi Arabia projected a total number of CVD cases in the country by 2035 and estimated an increase in economic burden to US$9.8 billion [18].…”
Section: Burden Of Ncds In Saudi Arabiamentioning
confidence: 99%
“…These have scarcely begun to be explored in the global literature, with one study relying solely on the Cochrane database of systematic reviews [13] and another covering a single NCD condition, diabetes [14]. Previous NCD reviews in the region have either had broader scope of inclusion criteria incorporating studies of various methodologies including primary studies [9], or were focused on a distinct theme in NCD research (e.g cost analyses or genetics in NCD research) [15,16] or a single country [17]. However, no previous study has appraised NCD-related evidence generated from exclusively systematic reviews.…”
Section: Introductionmentioning
confidence: 99%